Breastfeeding and infant care as ‘sexed’ care work: reconsideration of the three Rs to enable women’s rights, economic empowerment, nutrition and health - Gribble, Karleen D.; Smith, Julie P.; Gammeltoft, Tine; Ulep, Valerie; Van Esterik, Penelope; Craig, Lyn; Pereira-Kotze, Catherine; Chopra, Deepta; Siregar, Adiatma Y. M.; Hajizadeh, Mohammad; Mathisen, Roger (Frontiers in Public Health, 2023)
Women 1 's lifelong health and nutrition status is intricately related to their reproductive history, including the number and spacing of their pregnancies and births, and for how long and how intensively they breastfeed their children. In turn, women's reproductive biology is closely linked to their social roles and situation, including regarding economic disadvantage and disproportionate unpaid work. Recognising, as well as reducing and redistributing women's care and domestic work (known as the 'Three Rs'), is an established framework for addressing women's inequitable unpaid care work. However, the care work of breastfeeding presents a dilemma, and is even a divisive issue, for advocates of women's empowerment, because reducing breastfeeding and replacing it with commercial milk formula risks harming women's and children's health. It is therefore necessary for the interaction between women's reproductive biology and infant care role to be recognised in order to support women's human rights and enable governments to implement economic, employment and other policies to empower women. In this paper, we argue that breastfeeding -like childbirth -is reproductive work that should not be reduced and cannot sensibly be directly redistributed to fathers or others. Rather, we contend that the Three Rs agenda should be reconceptualised to isolate breastfeeding as 'sexed' care work that should be supported rather than reduced with action taken to avoid undermining breastfeeding. This means that initiatives towards gender equality should be assessed against their impact on women's ability to breastfeed. With this reconceptualisation, adjustments are also needed to key global economic institutions and national statistical systems to appropriately recognise the value of this work. Additional structural supports such as maternity protection and childcare are needed to ensure that childbearing and breastfeeding do not disadvantage women amidst efforts to reduce gender pay gaps and gender economic inequality. Distinct policy interventions are also required to facilitate fathers' engagement in enabling and supporting breastfeeding through sharing the other unpaid care work associated with parents' timeconsuming care responsibilities, for both infants and young children and related household work.